STUDENTS’ WRITING ERROR IN USING ENGLISH CAUSATIVE - Muh Dzul Izza Nawir; Syamsiarna Nappu; Ilmiah Ilmiah (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2019)
This research aimed to find out kinds of errors in the use of active and passive English causative in writing is made by the sixth-semester Students English Department at the Muhammadiyah University of Makassar. The method of this research was a correlation with the descriptive quantitative method. The instrument of this research was the writing test. This research took population was the sixth-semester students of English Department at Makassar Muhammadiyah University. This research used the random sampling technique. It is the ideal way to take sample objectively. The researcher took 5 to 6 students from each class by lottery. The total samples were 56 students. The result of the study signs students' error in two categories. They were students’ error in using active and passive English causative. The findings indicated 1107 errors in using active English causative, which the most dominant error is misformation with 578 times of appearances or 52.22%. Addition occupied the second place of the most dominant error with 430 times of appearances or 38.85%. Omission took the third place of the most dominant error with 80 times or 7.22%. Misordering occupied the last place of the most dominant errors with 19 times of appearances or 1.71%. While, the error in using passive English causative indicated 1194 error, which misformation is the most dominant error with 575 times of appearances or 48.16%. Addition occupied the second place of the most dominant error with 394 times of appearances or 33.00%. Furthermore, omission took the third place of the most dominant error with 127 times or 10.64%. Misordering occupied the last place of the dominant error with 98 times of appearances or 8.20%. Based on the research, the researcher concluded that students made the most dominant errors is misformation and the students rarely made misordering errors both are in using active English causative or passive English causative.